Narrowing range of concession period for build operate transfer highway project under public private partnership using bargaining game theory / Nur Hazwanie Mohamed Yusoff - Mohamed Yusoff, Nur Hazwanie (2016)
Public Private Partnership is one of the popular contracts used in building infrastructure in Malaysia. One of the important aspects in the contract is to find reasonable concession period which protect both government and private sectors from losing. This research provides a methodology to narrow the range of concession period that would benefit both government and private sectors taking the impact of risks into consideration. Required data for this research were obtained by interviewing representatives of private sector and retrieving annual report of the company that was available on Bursa Malaysia. The financial model was evaluated using Monte Carlo simulation on the computational software to compute Net Cash Flow and Net Present Value. The range of concession period for the private sectors and government to negotiate is generated by the simulation. In order to narrow the range of concession period, Bargaining Game Theory was employed. The benefit formulae proposed by L. Y. Shen, Bao, Wu, and Lu (2007) was modified by taking the average between two NPVs to suit the Malaysia case study. Therefore, the modified formulae provides fair benefit for both parties. To demonstrate the applicability of suggested methodology, Build Operate Transfer (BOT) highway project in Malaysia were used in this research. The narrowing concession period was found to be shorter than the actual concession period. Using the suggested methodology, government could further improve its policies in processing BOT projects thus, attract private sectors interest in infrastructure development.